Design and development of a cost effective urban resedential solar PV system - Hasan, Fahim; Hossain, Jakir; Rahman, Maria; Ar Rahman, Sazzad (BRAC University, 2011)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2010.